ADAPTIVE STRATEGIES FOR 21ST CENTURY LEARNING: DIGITAL LITERACY AND LEARNING OUTCOMES IN CONTEMPORARY INDONESIAN HIGHER EDUCATION - Susi Adiawaty; Markus Oci; Al-Amin; Siminto; Lilis Ermindyawati (International Journal of Teaching and Learning, 2023)
This research, conducted in the contemporary landscape of Indonesian higher education, investigated the dynamic interplay between digital literacy and learning outcomes. Employing a mixed-methods approach, the study sought to unravel the nuanced relationships between students' digital literacy levels, the integration of Massive Open Online Courses (MOOCs), and their impact on critical thinking skills and academic performance. The findings revealed a compelling positive correlation between digital literacy proficiency and enhanced learning outcomes, highlighting the pivotal role of digital literacy in preparing students for the challenges of the 21st century. Moreover, this study unveiled the diverse landscape of MOOC integration across various academic disciplines within Indonesian universities. The adoption of MOOCs was unique, varying significantly across fields of study. These variations emphasize the importance of tailored strategies and support systems to facilitate more equitable MOOC adoption. The implications of this research extend to policymakers and practitioners, emphasizing the need for comprehensive digital literacy initiatives and discipline- specific approaches to MOOC integration. By embracing these adaptive strategies, Indonesian higher education can position itself as a dynamic and responsive sector primed for the demands of the digital age. This research underscores the evolving landscape of education and the vital role of digital literacy in shaping the educational outcomes of Indonesian students.